INDONESIAN CAPITAL MARKET REACTIONS FOR THE ELECTION OF DONALD TRUMP AS UNITED STATES PRESIDENT (EMPIRICAL STUDY ON MULTINATIONAL COMPANIES LISTED ON THE INDONESIA STOCK EXHANGE) - Daniel Christopher; Layyinaturrobaniyah . (Journal of Management and Business, 2019)
This study aims to determine the market reaction to the announcement of the Donald Trump as the elected President of the United States, as seen from the performance of the shares of multinational companies on the Indonesia Stock Exchange (BEI) and tests market efficiency in a half-strong form. This research uses purposive sampling technique with samples of 24 multinational companies and uses a market model to calculate abnormal return. The results show that first, there are significant average abnormal returns at t-6, t-4, t-3, t-2, then at t + 1 to t + 7 and negative cumulative average abnormal returns. Second, there are smaller but significant average abnormal returns after Donald Trumph's announcement as President of the United States than average abnormal returns before the announcement during the window period. Third, trading volume activity decreases significantly after the announcement of Donald Trump as the elected President of the United States. The results of the research prove that the market reacts to the announcement of Donald Trump as the elected President of the United States or it can be said that the announcement has a negative information content on the performance of the stock market represented by the stock performance of multinational companies. In addition, these results prove that the Indonesian capital market is not efficient in half-strong form due to information leakage and reaction that is quite slow in responding to the announcement of Donald Trump as the elected President of the United States.